PENGARUH STRUKTUR MODAL, LIKUIDITAS DAN ARUS KAS BEBAS TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN - BUDI ISWOYO (AKADEMIKA, 2021)
This study is to find the effect of capital structure, liquidity and free cash flow to firm value with profitability as a moderating variable. Sample 12 companies taken by nonprobability sampling (purposive sampling) of 12 automotive companies and components listed on Indonesia Stock Exchange 2012-2016. The method of data analysis used in this research is explanatory, research with multiple regression approach with the help of SPSS 23. The result of research indicates that capital structure, liquidity, free cash flow of profitability as a moderation variable have no positive and significant influence to firm value and free cash flow have influence positive and significant to value firm.